Awareness Regarding Domestic Violence among Reproductive Age Women - Rana, Gayatri; Shrestha, Rajan (Journal of Karnali Academy of Health Sciences, 2019)
Background: Violence is a significant public health, human rights and human development problem. The objective of the study was to find out awareness regarding awareness domestic violence among reproductive age women. Methods: Descriptive, cross sectional research design was adopted and a total 100 reproductive age women were selected by purposive sampling technique in Devchuli municipality -1, Nawalparasi from 27 July to 31 July, 2015. Semi structured questionnaire was used to collect data. Descriptive (Frequency, percentage, median & quartile) and inferential statistics (Chi-square) was used to analyze data by using SPSS. Results: There was significant association between level of awareness regarding domestic violence and caste: Dalit (p=0.002) and religion (p=0.019). Hinduism were 3.165 (OR) & 4.210 (AOR) times more likely to have awareness regarding domestic violence than Non Hinduism, at OR (p=0.023) & AOR (p=0.136) respectively. Significant with level of education (p=0.005), reproductive age women who had basic level education were 1.111 (OR) & 1.319 (AOR) times more likely and who had secondary level were 0.867 & 0.921 times less likely to have awareness regarding domestic violence than women with non formal education, which was statistically not significant OR (p=0.869) & AOR (p=0.750) and significant at OR (p=0.014) & AOR (p=0.021) respectively; significant with family income (p=0.023), reproductive age women who had family income sufficient to eat for >1 year and surplus were 2.627 (OR) & 2.494 (AOR) times more likely to have awareness regarding domestic violence than sufficient to eat up to 1 year, at OR (p=0.024) & AOR (p=0.218) respectively; and significant with not involved in woman group/organization/political party (p=<0.001), reproductive age women who had not involved in woman group/organization/political party were 7.667 (OR) & 6.958 (AOR) times more likely to have awareness regarding domestic violence than who involved, which was statistically significant OR (p=<0.001) & AOR (p=0.021) respectively. Conclusion: Half of reproductive age women have good awareness regarding violence. There is significant association between level of awareness and caste, religion, level of education, family income and not involved in woman group/organization/political party.